Epidemiology of Pediatric Foreign Body Ingestions Amidst the Coronavirus 2019 Pandemic at a Tertiary Care Children's Hospital. Issue 1 (24th February 2022) - Klein, Lauren J.; Black, Katherine; Dole, Michael; Orsagh-Yentis, Danielle K.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: The coronavirus disease (COVID) 2019 pandemic and resultant stay-at-home orders altered caregivers' responsibilities and children's daily environments. We aimed to compare the epidemiology and morbidity of foreign body ingestions (FBIs) during the COVID pandemic and the prior year. Methods: We performed a retrospective review of children cared for at our tertiary care children's hospital for FBI from March to July 2019 (pre-COVID) and March to July 2020 (COVID). Cases were identified via a search of all diagnoses of foreign bodies (FBs) in the alimentary tract. Charts were reviewed to determine the types of FBs ingested and the patients' clinical courses. Results: A total of 71 encounters were identified. Thirty ingestions occurred in the pre-COVID cohort and 42 in the COVID cohort. One patient ingested 2 different FBs. There was a significantly higher rate of FBIs per day in May 2020 (COVID) compared with May 2019 (pre-COVID; 0.387 versus 0.161; P = 0.046). The median age at presentation was not significantly different between the two groups (pre-COVID, 63.8 months; COVID, 62.5 months; P = 0.78). FBs were located in the esophagus less frequently in the COVID cohort than in the pre-COVID cohort ( P < 0.01). Endoscopies were less frequently performed in the COVID cohort (52.4% versus 70.0%; odds ratio, 0.47; 95% CI, 0.15–1.40). Conclusions: The frequency of FBIs trended higher in the COVID cohort, with significantly more FBIs in May 2020 when compared with May 2019. Patients in the COVID cohort more frequently had FBs located beyond the esophagus, indicating later presentation and a lesser need for urgent endoscopic removal.